The British strategy of dealing with national sabotage and the allies’ economic interests through wartime import control in Nigeria, 1939-1945 (2021)
The outbreak of the Second World War in 1939 had far-reaching impact on the history of the world, including the deployment of new strategies of war, the stresses and strains of the global economy and a global call for decolonisation. Through their works, historians, political scientists, sociologists, and economists have examined the developments that unfolded during the war. The mobilisation of the Allied powers’ resources against the Axis powers, the bombardments of the enemy’s territories within and outside Europe, the initial success of the Axis in the early stages of the war are typical examples of the developments that manifested during the Second World War. Similarly, scholars such as Kehinde Faluyi and Ayodeji Olukoju have interrogated the effects of the war on Africa, the various policies of the European powers in their respective colonies during the war, the mobilisation of human and material resources of these African colonies for war efforts, the impact of the war on the economy of the African continent as a whole, the nature of food supply from Nigeria as a colony for metropolitan war efforts and the intensification of economic blockade against the Axis’ economic presence in Africa in general and Nigeria in particular. These intellectual efforts seem to have neglected how the British used import control in Nigeria as a wartime tool for dealing with metropolitan sabotage adopted against the British war effort and the intensification of economic blockade against the British wartime allies in Nigeria. The paper argues that the British deployed import control to curb the national sabotage of the manufacturers in Britain and restrict the economic presence of their allies during the war.